Approximate test risk minimization through soft margin estimation - Li, Jinyu (Proc. ICASSP, 2007)
In a recent study, we proposed soft margin estimation (SME) to learn parameters of continuous density hidden Markov models (HMMs). Our earlier experiments with connect digit recognition have shown that SME offers great advantages over other state-ofthe- art discriminative training methods. In this paper, we illustrate SME from a perspective of statistical learning theory and show that by including a margin in formulating the SME objective function it is capable of directly minimizing the approximate test risk, while most other training methods intent to minimize only the empirical risks. We test SME on the 5k-word Wall Street Journal task, and find the proposed approach achieves a relative word error rate reduction of about 10% over our best baseline results in different experimental configurations. We believe this is the first attempt to show the effectiveness of margin-based acoustic modeling for large vocabulary continuous speech recognition. We also expect further performance improvements in the future because the approximate test risk minimization principle offers a flexible and yet rigorous framework to facilitate easy incorporation of new margin-based optimization criteria into HMM training.